The Role of Business Communication in Handling Climate Change Issues to Support SDG’s - Kusuma, Ajeng Nisa; Wibowo, Kunto Arief (Commercium : Journal of Business and Management, 2024)
Climate change occurs due to long-term changes in temperature and atmosphere, one of the obvious examples of climate change is global warming that is increasing in every region of the world and this reaches dangerous levels. The world of business people has always attached importance to a profit from the business that is being run, but they do not think about how environmental changes can have a big impact later on business people. This study uses qualitative research with a literature study method and the use of articles that provide relevance. The results of this study provide an explanation that the role of business communication in handling climate change in order to be able to implement the SDGs is through transparency, awareness education, green marketing and also partnership collaboration. Business communication is the main foundation because it can provide an effective flow, inform and also mobilize as a stakeholder in taking action to be able to fight climate change.